Design of a protocol for the pharmacovigilance process in the Camilo Ponce Enríquez health center - Ganán Aguilar, Enrique Oswaldo; Arias Duque, Luis Armando (Revista Universidad de Guayaquil, 2021)
Pharmacovigilance determines a public health action that identifies, evaluates and prevents the risks arising from the use of drugs. The present study is developed with the objective of designing a Pharmacovigilance protocol applicable in the Ponce Enríquez Health Center, Azuay province; this in order to obtain knowledge that allows managing the early detection of a RAM FT y EM. The methodology constitutes a descriptive and documentary research, where the survey of a population that was made up of 40 health professionals was used as a technique. The results that were identified were that 80% of the professionals were unaware of the SNFV regulations, 80% of them were unaware of the information sources of the VF and 92.5% of the respondents were unaware of the structure of the SNFV (92.5); Furthermore, 37.5% of the professionals were unaware of the detection of ADRs. On the other hand, 21 cases were analyzed within a data matrix of the CPE health center where 85.7% of them constitute ADRs and the remaining 14.3% refer to FT. Tramadol was the predominant suspect drug with 23.8%; and the preeminent ADRs were allergic rash and nausea. The implementation of a VF protocol is established as a necessary tool that enables the correct notification of adverse drug events in patients.